2010
DOI: 10.1111/j.1741-6612.2010.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in fall‐related injury hospitalisations and trauma presentations

Abstract: Falls, particularly for older individuals, are an important cause of serious injury, representing a considerable burden in terms of hospitalised morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
(19 reference statements)
3
11
2
3
Order By: Relevance
“…Our study shows that falls at home affect all age groups, but are most common in the elderly [3, 6, 13, 14]. Sartini et al [3] reported slightly lower figures than ours, with 46.3% of all falls occurring at home.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Our study shows that falls at home affect all age groups, but are most common in the elderly [3, 6, 13, 14]. Sartini et al [3] reported slightly lower figures than ours, with 46.3% of all falls occurring at home.…”
Section: Discussioncontrasting
confidence: 58%
“…Throughout the world, falls are a major public health problem and a socioeconomic burden [16]. Approximately one-third of the population over the age of 65 falls each year, rising to over 50% by the age of 80 [5, 710].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, older adults are in general risk averse (Albert and Duffy, 2012; Tymula et al, 2013) and risk-sensitivity has been shown to influence sensorimotor control (Nagengast et al, 2010; O'Brien and Ahmed, 2015) and motor adaptation (Trent and Ahmed, 2013). Thus, it is possible that the aged motor system exploits prior experiences rather than exploring new movements to avoid risks such as falling, which have more serious consequences in old than young populations (Talbot et al, 2005; Mitchell et al, 2010). In sum, older adults need to accumulate a lot of evidence in a new environment before updating their movements possibly due to large sensory and motor noise or their fear of risks associated to movement exploration.…”
Section: Discussionmentioning
confidence: 99%
“…According to worldwide statistics in 2000, approximately 283,000 people were injured seriously from falls [1]. More than 50% of seniors with a history of falls experience them again [2], and 25% appear to have restrictions in their activities of daily living (ADL) due to physical injury and fear of falling.…”
Section: Introductionmentioning
confidence: 99%